Dinosaur mountain : digging into the Jurassic Age - Ray, Deborah Kogan, 1940- (New York : Farrar Straus Giroux, 2010)
An illustrated story of early twentieth-century dinosaur hunter, Earl Douglass, who discovered a treasure trove of prehistoric bones and fossils in northeaster Utah.
"Frances Foster books."
Includes bibliographical references.
Booklist
Publisher's Weekly
School Library Journal starred
Booklist, February 2010
Keywords: Dinosaurs -- Colorado -- Juvenile literature; Dinosaurs -- Utah -- Juvenile literature; Paleontology -- Colorado -- Juvenile literature; Paleontology -- Utah -- Juvenile literature; Dinosaurs -- Colorado; Dinosaurs -- Utah; Paleontology -- Colorado; Paleontology -- Utah; Dinosaurs -- Colorado; Dinosaurs -- Utah; Paleontology; Dinosaur National Monument (Colo. and Utah) -- History -- Juvenile literature; Dinosaur National Monument (Colo. and Utah) -- History; Dinosaur National Monument (Colo. and Utah) -- History; Picture books for children